Neurosains dalam Pembelajaran Agama Islam - Dewi, Citra Trisna; Fitri, Nur Wulandari; Soviya, Ovi (Ta'allum: Jurnal Pendidikan Islam, 2018)
This article discuss neuroscience in Islamic religion learning. Islamic religious science is concerned with neuroscience because neuroscience studies the brain. Brain is the center of human intelligence that controls the nervous system in capturing a learning. The clearer the goal of learning religious education the easier the selection and determination of materials and methods of delivery. Islamic education through neuroscience theory can be done by teachers or educators must first know and understand the performance of the human brain, taking into account the natural work of the learners' brain in the learning process, creating an atmosphere of learning in which learners are respected and supported, avoiding the occurrence pemforsiran to work the brain, after that, the PAI teacher can use various learning models of Islamic Education that are interesting to students or learners. Thus, students will experience optimization of brain function properly and correctly so that learning objectives can be achieved well.